First records of egg phoretic flies of Dermatobia hominis (Linnaeus, 1781) (Diptera: Cuterebridae) in Ecuador - Alex Pazmiño-Palomino; Cristhian Cusicondor-Loza (Revista Chilena de Entomología)
Myiasis is a widely known human and veterinary public health problem in tropical and subtropical America. Dermatobia hominis (L.) is the main species causing myiasis. This fly deposits its eggs on the bodies of other hematophagous dipterans, which transport them to their vertebrate hosts. Knowing and monitoring the phoretic flies of D. hominis eggs is a part of myiasis control to avoid long-term economic losses in animal production. Samples were collected with hand nets and Malaise traps at five localities in the Pacific slopes of the Andes and four on the Amazonian slopes. Here we publish the first scientific information about the species of egg phoretic flies of D. hominis in Ecuador. We identified four species transporting eggs: Sarcopromusca pruna (Shannon and Del Ponte), Stomoxys calcitrans (L.) (Muscidae), Fannia sp. (Fanniidae) and Chrysops varians tardus Wiedemann (Tabanidae). We present the first record of S. pruna from Ecuador and the first record of C. varians tardus as a carrier of D. hominis eggs. Our results included the abundance of flies acting as carriers along different months, the number of eggs attached to the phoretic fly body. Finally, we discuss the importance of continuing research on phoretic flies of D. hominis eggs in Ecuador.